Efeitos do ambiente sobre as variáveis fisiológicas e perda de calor latente em cutias (Dasyprocta aguti; Linnaeus, 1766) em uma região semi-árida - Queiroz, João Paulo Araújo Fernandes de (2010)
This study aimed to evaluate the effects of environment on the physiological variables in agouti (Dasyprocta aguti; Linnaeus, 1766) and determine the heat loss by evaporation of this rodent. The respiratory rate had a significant effect (P<0.05) of the sex, with males being those with the highest average. Only age had significant effect (P<0.05) on rectal temperature, with the young exhibiting an average temperature higher than the adults. The right tympanic temperature was affected by sex at a significance level of 5% probability, with females having the higher average temperatures. In different ages and sexes groups, the right tympanic temperature remained above the left tympanic temperature. The temperature of the body surface had a significant effect (P<0.05) of the interaction (Sex with Age). The animal´s effect occurred while the black globe temperature in the shade remained below 32o C. Preliminary results on the distribution of body surface temperature showed significant effect (P<0.01) of body regions evaluated, with the ears (37.40±0.04° C) and the hind feet (35.89±0.04o C) had higher average temperatures. Histological analysis of skin did not reveal the presence of sweat glands. The mechanisms of latent heat loss was not affected by sex and age and showed no significant correlation with the meteorological variables. The mean and standard deviation for the heat loss by evaporation in agouti was 10.76±6.67 Wm-2.